Development of a solar tracking system of a nonelectric power source by using a metal hydride actuator. (December 2017) - Obara, Shin'ya; Matsumura, Kazuhiro; Aizawa, Shun; Kobayashi, Hiroyuki; Hamada, Yasuhiro; Suda, Takanori
Highlights: Solar tracking system with metal hydride of nonelectric power source was developed. Proposed new solar tracking system is driven by hydrogen equilibrium pressure. Increase of 7.2% in production of electricity was achieved by the proposed system. Tracking accuracy and the improvement task of the proposed system were clarified. Abstract: This study develop the solar tracking system of a nonelectric power source by using a metal hydride (MH) actuator with solar radiation drive. The proposed tracking system includes two MH reactors of the same shape that are placed perpendicular to the solar cell array. A shielding plate is installed between the MH reactors to interrupt the solar radiation from each MH reactor. The solar angle of direction changes when there is a temperature difference between the MH reactors. This is because a gap occurs in the equilibrium pressure of the hydrogen sealed hermetically in each reactor, and the actuator angle of direction follows the sun according to this pressure difference. This study also present the result of the proposed system after four months of testing. Moreover, this study examine the wind's influence on the proposed MH actuator by applying heat fluid simulation. In order to achieve highly reliable solar tracking with the proposed system, excessive cooling by wind should be prevented by installing a windshield.